A Compact SIW Mixer For Millimeter-Wave Applications - Abdelkhalek Nasri; Hassen Zairi; Ali Gharsallah (International Journal of Electrical and Computer Engineering (IJECE), 2014)
The present paper highlights an innovative broadband millimeter-wave single balanced diode mixer which is designed using a newly designed 90 substrate integrated waveguide (SIW) coupler and two cavity (SIW) filters. The mixer covers RF/LO operating frequency range which fluctuates between 10 to 12 GHz and IF port covers 2GHz. The proposed mixer exhibits a fairly low conversion loss of less than 10 dB and high port to-port isolations over the frequency band of interest as the simulated results make clear. Furthermore, the two cavities SIW filter is embedded to achieve a better image frequency suppression of about 28dB.DOI:http://dx.doi.org/10.11591/ijece.v4i6.6684